Organic nitrogen in a typic hapludox fertilized with pig slurry Frações De Nitrogênio Orgânico Em Latossolo Vermelho Adubado Com Dejeto Suíno - Grohskopf M.A.* (2015)
© 2015, Revista Brasileira de Ciencia do Solo. All rights reserved.The application of pig slurry may have a different effect on nitrogen dynamics in soil compared to mineral fertilization. Thus, the aim of this study was to determine the different forms of organic N in a Latossolo Vermelho distroférrico (Typic Hapludox) and their relationship to N uptake by crops in response to 10 years of annual application of pig slurry and mineral fertilizer. The treatments were application rates of 0, 25, 50, 100, and 200 m3 ha-1 of pig slurry, in addition to mineral fertilizer, organized in a randomized block design with four replications. The N contents were determined in the plant tissue and in the forms of total N and acid hydrolyzed fractions: ammonium-N, hexosamine-N, α-amino-N, amide-N, and unidentified-N. Annual application of pig slurry or mineral fertilizer increased the total-N content in the 0-10 cm depth layer. The main fractions of organic N in the soil were α-amino-N when pig slurry was applied and unidentified-N in the case of mineral fertilizers. Pig slurry increased the N fractions considered as labile: α-amino-N, ammonium-N, and amide-N. The increase in these labile organic N fractions in the soil through pig slurry application allows greater N uptake by the maize and oat crops in a no-tillage system.